Pengaruh Transaksi Pihak-pihak Istimewa terhadap Manajemen Laba: Kepemilikan Institusional sebagai Variabel Moderasi - Robert Jao; Paulus Tangke; Anthony Holly; Jackson Thungadi; Lasty Agustuty (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
The purpose of this study was to investigate the effect of related party transactions on earnings management. This study also investigates the role of institutional ownership as a moderator on the effect of related party transactions on earnings management. This study uses agency theory to explain the relationship between variables. The research population consists of all manufacturing companies listed on the Indonesia Stock Exchange. The sample selection used a purposive method which produced 225 observational data. The analytical method used is moderation regression analysis. The results of this study indicate that partially related party transactions have a positive and significant effect on earnings management. Institutional ownership is able to significantly weaken the relationship between related party transactions on earnings management and act as a quasi moderator.